Electronic Customer Relationship Management and Browsing: Driving Electronic Word of Mouth in Indonesia’s Online Marketplace - Diana Anggraeni (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study delves into the effects of Electronic Customer Relationship Management (e-CRM), hedonic and utilitarian browsing on e-satisfaction, and their influence on electronic Word of Mouth (eWOM) in Indonesia's online marketplace. The digital commerce landscape emphasizes e-CRM's importance in managing customer interactions. Surveying 962 active users, this quantitative study reveals significant links between browsing behaviors and e-satisfaction, underlining diverse user preferences. Positive associations with eWOM suggest satisfied users advocate for brands. However, e-CRM shows non-significant ties with user satisfaction or eWOM, indicating the need for refined strategies aligned with user expectations. Theoretical implications support established models, offering insights into consumer behavior. This research enriches understanding of Indonesian online shopping, guiding tailored marketing communication strategies to boost satisfaction and eWOM endorsements. Future research could explore additional factors and strategies to optimize online retail experiences.